Market Integration and Financial Crisis: New Evidence from Asian Paciic Markets - Atmadja, Adwin Surja; Wu, Yanhui; Juli, Wan (The Indonesian Capital Market Review, 2010)
We investigated the stock market integration among national equity indices in eight countries from the period of 1995 to 2009, which was then clustered into four sub-sample periods. The multivariate time series analyses were employed to observe the degree and the existence of the integration. We found a cointegrating vector in each of three sub-sample periods. Interestingly, in the 1997 inancial crisis, we found that there was no indication of cointegration relationship among the equity indices. The results of block causality tests and the accounting innovation analysis indicate that the short run dynamic interactions among the stock indices became more intense during the current inancial crisis, and that the U.S. stock market played dominant role in the regional markets.